Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Photo-assisted catalytic oxidation using PBA-derived ZnCo oxides in a H₂O₂ system for organic pollutant removal - Jia-Yin Lin; Yun-Ju Lai; Ying-hua Lai; Ta Cong Khiem; Nai-Wen Tsao; Yu-Chih Tsai (Journal of Water Process Engineering, 2026)

Climate change reshapes the dominant drivers of endorheic lakes on the Qinghai-Tibet Plateau - Hui Lin; Xuegao Chen; Nan Xu; Qin Ju; Jingcai Wang; Huanghe Gu; Tongqing Shen; Zhongxiang Wang; Xingrong Si; Jinguo Wang; Zhongbo Yu (Global and Planetary Change, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Multi-source isotopic tracing reveals meltwater runoff processes and environmental responses in the Yarlung Tsangpo River Basin - Zijun Zhang; Xuegao Chen; Hui Lin; Tongqing Shen; Qin Ju; Shiqin Xu; Ningpeng Dong; Peng Yi; Peng Chen; Naifeng Zhang; Yong Huang; Jinguo Wang; et al. (Journal of Hydrology, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Genome-wide characterization of the TCP family in Lagerstroemia and functional analysis of LfiTCP12 uncover its role in shoot branching promotion - Yan Xu; Ye Zhang; Chengzhi Li; Ruixia Yin; Hang Lin; Yu Zuo; Xin Huang; Bo Qin; Yiqian Ju (Plant Cell Reports, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Decadal variations in the northern boundary of permafrost in the Xidatan region of the Qinghai-Xizang Plateau: Insights from InSAR and field monitoring - Ju Xin; Luo Jing; Niu Fujun; Yu Fan; Ding Zekun; Yin Guoan; Lin Zhanju; Gao Zeyong (Cold Regions Science and Technology, 2026)

Oroxin A suppresses non-small cell lung cancer via the HSP90AA1/AKT signaling pathway - Mingxiao Wang; Yong Zhang; Ruoyang Liu; Juan Lin; Tengfei Wang; Huijun Dong; Ju Yang; Xiuyuan Li; Dehai Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Host-mediated environmental microbiome recruitment by black soldier fly (Hermetia illucens) enhances waste biotransformation - Zhe Li; Yuchen Zhou; Lin Lv; Yinguang Long; Mengyao Dong; Qi Xiao; Xianyue Jia; Dechen Ju; Xiaowen Sun; Feng Huang; Minmin Cai; Jibin Zhang; et al. (Waste Management, 2025)

Novel xylanase activity and biofuel production in Lacrimispora xylanolytica isolated from termite guts symbionts - Chia-Chi Yang; Yu-Ju Lin; Fu-Shyan Wen (Bioresource Technology, 2025)

Deep learning reveals the relationship between vegetation and runoff in the Weihe River Basin on the Loess Plateau - Qin Ju; Wenjie Zhao; Tongqing Shen; Junliang Jin; Hui Lin; Xiaoni Liu; Peng Jiang; Jianhui Wei; Zhongbo Yu (Hydrological Sciences Journal, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Enhanced selective sorption of Cu(II) from washing solution of fly ash using polyethyleneimine-crosslinked chitosan sorbents - Yu Gong; Zitao Lin; Jing Yang; Yongming Ju; Dorota Kołodyńska; Jie Liu; Xiaohan Shan; Yujie Wang; Yong Zhang; Weixin Li (Chemical Engineering Journal, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Insight into selective removal of trace thallium (Tl(Ι)) by novel chitosan adsorbents encapsulating low-cost silicate mineral wastes - Yu Gong; Yujie Wang; Jing Yang; Yongxin Bing; Zifei Sun; Yongming Ju; Xiaochen Lin; Houhu Zhang; Zitao Lin; Weixin Li (Environmental Research, 2025)

Co-adsorption of methylene blue/Pb(II) from aqueous solutions using sulfonated mesoporous diatomite - Ali M. Abou-Elanwar; So Young Lee; Jeongkyun Yu; Jieun Kim; Chihyun Hwang; Hyungmin Park; Young-tai Noh; Ming Xie; Jiuyang Lin; Seong-Ju Park; Dong Han Seo; Youngjin Kim (Journal of Water Process Engineering, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Lake responses and mechanisms to El Niño on the Tibetan Plateau using deep learning-based semantic segmentation - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen; Jingcai Wang (Journal of Hydrology, 2024)

From agricultural biomass to D form lactic acid in ton scale via strain engineering of Lactiplantibacillus pentosus - Chia-Chi Yang; Chia-Hau Chou; Gia-Luen Guo; Yu-Ju Lin; Fu-Shan Wen (Bioresource Technology, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Two-Level regulation photocatalytic activity of Bi2WO6/COFs with ligand engineering and piezoelectric field for Highly-Efficient degradation of antibiotics - Yujun Ju; Hailong Lin; Chen Chen; Ruien Hou; Zhe Wang; Tinglong Hao; Min Xu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

Efficiencies of filtration sampling and extraction for recovery of viable Staphylococcus aureus bioaerosols - Ching-Wen Chang; Yen-Ni Lin; Sheng-Hsiu Huang; Yu-Ju Horng (Journal of Aerosol Science, 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Preliminary assessments of population exposure to glycidyl esters and 3-monochloropropane-1,2-diol esters from miscellaneous oil-containing packaged foods in Taiwan - Yu-Hsuan Chang; Kai-Wei Liao; Zih-Ee Lin; Wei-Ju Lee (Food Chemistry, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Frozen carbon is gradually thawing: Assessing interannual dynamics of thawed soil organic carbon stocks in the Tibetan Plateau permafrost area from 1901−2020 - Tongqing Shen; Peng Jiang; Qin Ju; Xuegao Chen; Hui Lin; Jiahui Zhao; Fan Zhang; Zhongbo Yu (Agricultural and Forest Meteorology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Spatial-temporal dynamics of meteorological and soil moisture drought on the Tibetan Plateau: Trend, response, and propagation process - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen (Journal of Hydrology, 2023)

Dendrobium officinale aqueous extract regulates bile acid synthesis to improve acute alcoholic liver injury in mice - Ju Ye; Di Wu; Xingdong Wu; Lin Qin; Mengting Yang; Yan-liu Lu; Dao-peng Tan; Yu-qi He (Food Bioscience, 2023)

Sequential deacetylation/self-gelling chitin hydrogels and scaffolds functionalized with fucoidan for enhanced BMP-2 loading and sustained release - Hsien-Tsung Lu; Chi Lin; Yi-Ju Wang; Fang-Yu Hsu; Ju-Ting Hsu; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials - Zhe Zhao; Shumin Lin; Zhendong Yu; Ming Su; Bolong Liang; Shu-Xuan Liang; Xue-Hai Ju (Chemosphere, 2023)

Changes in permafrost spatial distribution and active layer thickness from 1980 to 2020 on the Tibet Plateau - Tongqing Shen; Peng Jiang; Qin Ju; Zhongbo Yu; Xuegao Chen; Hui Lin; Yueguan Zhang (Science of The Total Environment, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Diagnostic approaches and contribution of next-generation sequencing technologies in genomic investigation of Vibrio parahaemolyticus that caused acute hepatopancreatic necrosis disease (AHPND) - Lean Huat Yu; Cindy Shuan Ju Teh; Kien Pong Yap; Kwai Lin Thong (Aquaculture International, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Technology-side carbon abatement cost curves for China’s power generation sector - Lin-Ju Chen; Zhen-Hai Fang; Fei Xie; Hai-Kuo Dong; Yu-Heng Zhou (Mitigation and Adaptation Strategies for Global Change, 2020)

Nitrous oxide emissions from tea garden soil following the addition of urea and rapeseed cake - Jialuo Yu; Shan Lin; Muhammad Shaaban; Wenliang Ju; Linchuan Fang (Journal of Soils and Sediments, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Correction to: Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2020)

Gallic Acid Attenuated LPS-Induced Neuroinflammation: Protein Aggregation and Necroptosis - Yu-Ling Liu; Chia-Chi Hsu; Hui-Ju Huang; Chih-Jung Chang; Shu-Hui Sun; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Neuroprotective Effects of Baicalein on Acrolein-induced Neurotoxicity in the Nigrostriatal Dopaminergic System of Rat Brain - Wei-Zhong Zhao; Hsiang-Tsui Wang; Hui-Ju Huang; Yu-Li Lo; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

Design of wireless multi-parameter monitoring system for oral feeding of premature infants - Yu-Lin Wang; Hsing-Chien Kuo; Lin-Yu Wang; Mei-Ju Ko; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

2.5D induced polarization forward modeling using the adaptive finite-element method - Yi-Xin Ye; Yu-Guo Li; Ju-Zhi Deng; Ze-Lin Li (Applied Geophysics, 2014)

Motor skill learning enhances the expression of activity-regulated cytoskeleton-associated protein in the rat cerebellum - Dean-Chuan Wang; Yu-Yi Lin; Tsan-Ju Chen; Hwai-Ting Lin (Journal of Comparative Physiology A, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

Temporal characteristics of black carbon concentrations and its potential emission sources in a southern Taiwan industrial urban area - Yu-Hsiang Cheng; Chi-Chi Lin; Jyh-Jian Liu; Cheng-Ju Hsieh (Environmental Science and Pollution Research, 2014)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Isolation and characterization of polymorphic microsatellite loci in Candidia barbata (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Yu-Min Ju; Lee-Shing Fang; Chung-Jian Lin (Conservation Genetics, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

Cloning, Structure, and Expression Pattern of the P-450 Aromatase Gene in Rice Field Eel (Monopterus albus) - Ju-Hua Yu; Yong-Kai Tang; Jian-Lin Li (Biochemical Genetics, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)